The κ-opioid receptor-induced autophagy is implicated in stress-driven synaptic alterations - Karoussiotis, Christos; Sotiriou, Aggeliki; Polissidis, Alexia; Symeonof, Alexandra; Papavranoussi-Daponte, Danae; Nikoletopoulou, Vassiliki; Georgoussi, Zafiroula (Frontiers in Molecular Neuroscience, 2022)
Recent evidence has shown that G protein-coupled receptors (GPCRs) are direct sensors of the autophagic machinery and οpioid receptors regulate neuronal plasticity and neurotransmission with an as yet unclarified mechanism. Using in vitro and in vivo experimental approaches, this study aims to clarify the potential role of autophagy and κ-opioid receptor (κ-OR) signaling on synaptic structure and integrity. We hereby demonstrate that the selective κ-OR agonist U50,488H, induces autophagy in a time-and dose-dependent manner in neuronal cells by upregulating microtubule-associated protein Light Chain 3-II (LC3-II), Beclin1 and Autophagy Related Gene 5 (ATG5). Pretreatment of neuronal cells with pertussis toxin blocked the above κ-OR-mediated cellular responses. Our molecular analysis also revealed a κ-OR-driven upregulation of becn1 gene through ERK1,2-dependent activation of the transcription factor CREB in neuronal cells. Moreover, our studies demonstrated that sub-chronic U50,488H administration in mice causes profound increases of specific autophagic markers in the hippocampus with a concomitant decrease of several pre- and post-synaptic proteins such as spinophilin, postsynaptic density protein 95 (PSD-95) and synaptosomal associated protein 25 (SNAP25). Finally, using acute stress, a stimulus known to increase the levels of the endogenous κ-OR ligand dynorphin, we are demonstrating that administration of the κ-ΟR selective antagonist, nor-binaltorphimine (norBNI), blocks the induction of autophagy and the stress-evoked reduction of synaptic proteins in the hippocampus. These findings provide novel insights about the essential role of autophagic machinery into the mechanisms through which κ-OR signaling regulates brain plasticity.